China’s practice from coastline management towards sea-land integration - Zhao, Qiwei; Teng, Xin; Meng, Xue; Du, Zeming; Zhang, Panpan; Kang, Wanchao (Frontiers in Marine Science, 2025)
Integrated Sea-land management is an important feature of ecosystem-based management, and it is also the trend of marine spatial planning. China is one of the first countries worldwide to implement marine spatial planning which is mainly expressed as marine functional zoning (MFZ), and it has established a coastline management system for the connection between marine management and land management. In this paper, 18 national and local coastline management policies in China are analyzed. It is concluded that coastline management ensures the formulation, implementation, evaluation, and revision of MFZ, promotes the extension of MFZ to land, gradually evolves into coastal zone planning based on coordinated land and marine development, and promotes sea-land integration management in China. Taking Tangshan City in Hebei Province as an example, it is further proven that at the local level, coastline management accelerates the progress of sea-land integration.